At return to play following hamstring injury the majority of professional football players have residual isokinetic deficits. Issue 18 (3rd February 2014) - Tol, Johannes L; Hamilton, Bruce; Eirale, Cristiano; Muxart, Patrice; Jacobsen, Philipp; Whiteley, Rod
Abstract : Background: There is an ongoing debate regarding the optimal criteria for return to sport after an acute hamstring injury. Less than 10% isokinetic strength deficit is generally recommended but this has never been documented in professional football players after rehabilitation. Our aim was to evaluate isokinetic measurements in MRI-positive hamstring injuries. Methods: Isokinetic measurements of professional football players were obtained after completing a standardised rehabilitation programme. An isokinetic strength deficit of more than 10% compared with the contralateral site was considered abnormal. Reinjuries within 2 months were recorded. Results: 52 players had a complete set of isokinetic testing before clinical discharge. There were 27 (52%) grade 1 and 25 (48%) grade 2 injuries. 35 of 52 players (67%) had at least one of the three hamstring-related isokinetic parameters that display a deficit of more than 10%. The percentage of players with 10% deficit for hamstring concentric 60°/s, 300°/s and hamstring eccentric was respectively 39%, 29% and 28%. There was no significant difference of mean isokinetic peak torques and 10% isokinetic deficits in players without reinjury (N=46) compared with players with reinjury (N=6). Conclusions: When compared with the uninjured leg, 67% of the clinically recovered hamstring injuries showed at least one hamstring isokinetic testing deficit of more than 10%. Normalisation of isokinetic strength seems not to be a necessary result of the successful completion of a football-specific rehabilitation programme. The possible association between isokinetic strength deficit and increased reinjury risk remains unknown.